Measuring long-horizon security price performance - Kothari, S.P.; Warner, Jerold B. (Journal of Financial Economics, 1997)
Our simulation results show that tests for long-horizon (i.e.. multi-year) abnormal security returns around firm-specific events are severely misspecified. The rejection frequencies using parametric tests sometimes exceed 30% when the significance level of the test is 5%. Our results are robust to many different abnormal-return models. Conclusions from long-horizon studies require extreme caution. Nonparametric and bootstrap tests are likely to reduce misspecification.